Pendampingan Literasi Digital untuk Mengurangi Risiko Kejahatan Siber Membentuk Masyarakat yang Lebih Aman - M. Syafiih; Nadiyah; Khairi, Matlubul; Moh. Furqan; Beny Yusman (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
This community service activity aims to improve digital literacy and cybersecurity awareness in Paiton Sub-district as a response to the increasing risk of cybercrime in the community. The approach used involves the Participatory Action Research (PAR) method by involving various stakeholders, including the sub-district government, education office, and caregivers of Islamic boarding schools. The mentoring process includes a series of activities such as intensive training, interactive workshops, awareness campaigns through various media, as well as individual and group mentoring. These activities are designed to provide the Paiton community with a deep understanding of cyber threats, personal data protection techniques, and digital ethics. The results of these activities show significant improvements in digital literacy and changes in community behavior in using technology more safely. The formation of new institutions in the form of community groups and local cybersecurity teams is also evidence of the effectiveness of this collaborative approach. In conclusion, this service activity succeeded in creating social transformation by raising collective awareness of the dangers of cybercrime and producing a community that is more skilled in facing modern digital challenges. This program is expected to serve as a model for similar efforts in other regions to improve digital security and broader community welfare.